2019
DOI: 10.3892/mmr.2019.9856
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ACTA2‑AS1 promotes liver cancer cell proliferation, migration and invasion

Abstract: Long noncoding RNAs (lncRNAs) are important regulators of various cellular and biological processes. The present study aimed to investigate the functions of a novel lncRNA, ACTA2-AS1:4, a transcript variant of smooth muscle α-actin 2-antisense 1 (ACTA2-AS1), in regulating liver cancer progression. Expression of lncRNAs in liver cancer tissues and cell lines were analyzed by reverse transcription quantitative polymerase chain reaction (RT-qPCR). Knockdown of ACTA2-AS1:4 expression in LM3 liver cancer cells was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…ACTA2-AS1, also named as ZXF1, UC001kfo, and uc001kfo.1 (Gene id: 100132116), is a lncRNA consisting of five exons, located at GRCh38, 10q23.31. Recent studies revealed that ACTA2-AS1 was correlated with the development of several cancers such as liver cancer [ 11 ], lung adenocarcinoma [ 12 ], hepatocellular carcinoma [ 13 ] and breast cancer [ 14 ]. However, whether ACTA2-AS1 plays a role in the development of CC and the exact mechanism of its role remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ACTA2-AS1, also named as ZXF1, UC001kfo, and uc001kfo.1 (Gene id: 100132116), is a lncRNA consisting of five exons, located at GRCh38, 10q23.31. Recent studies revealed that ACTA2-AS1 was correlated with the development of several cancers such as liver cancer [ 11 ], lung adenocarcinoma [ 12 ], hepatocellular carcinoma [ 13 ] and breast cancer [ 14 ]. However, whether ACTA2-AS1 plays a role in the development of CC and the exact mechanism of its role remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…According to bioinformatics analysis, lncRNA actin alpha 2, smooth muscle antisense RNA 1 (ACTA2-AS1) is lowly expressed in tissue samples of stomach adenocarcinoma (STAD). In previous studies, ACTA2-AS1 acts as an oncogene in cervical cancer and ovarian cancer, while serving as antioncogene in liver cancer and lung adenocarcinoma [ 15 , 16 , 17 , 18 ]. However, the functions and mechanism of ACTA2-AS1 in GC have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…LINC00261 plays an antitumor role in LUAD through inducing DNA damage response (Shahabi et al, 2019). ACTA2‐AS1 is a newfound lncRNA that can act as a tumor suppressor in liver cancer 2019; nevertheless, its influences on LUAD progression remain to be investigated. Our current study first unveiled the role of ACTA2‐AS1 in modulating LUAD cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal expression of lncRNAs can affect the tumorigenesis or development of malignant tumors, such as lung cancer (Ye, Liu, & Zheng, 2017), hepatocellular carcinoma (Ding, Yang, & Yang, 2018), and squamous cell carcinoma of the head and neck (Di Agostino et al, 2018). Actin alpha 2, smooth muscle antisense RNA 1 (ACTA2‐AS1) is a lncRNA that has been revealed to be a tumor suppressor in liver cancer (Zhou & Lv, 2019); nevertheless, its influences on LUAD progression remain to be investigated. In our current study, we focused on the role of ACTA2‐AS1 in modulating LUAD cell functions.…”
Section: Introductionmentioning
confidence: 99%